Central nervous system involvement in Erdheim-Chester disease: An observational cohort study. (17th November 2020) - Cohen Aubart, Fleur; Idbaih, Ahmed; Galanaud, Damien; Law-Ye, Bruno; Emile, Jean-François; Charlotte, Frédéric; Donadieu, Jean; Maksud, Philippe; Seilhean, Danielle; Amoura, Zahir; Hoang-Xuan, Khê; Haroche, Julien
Abstract : Objective: CNS involvement in Erdheim-Chester disease (ECD) leads to substantial morbidity and mortality. To assess CNS manifestations in a French cohort of 253 patients with ECD, we determined clinical characteristics and outcomes, including those under targeted therapies. Methods: This was a retrospective longitudinal study. CNS manifestations were determined by clinical examination and brain or spine MRI. Targeted therapy efficacy was assessed using global assessment from a physician and a radiologist. The study was approved by the ethics committee Comité de Protection des Personnes Ile de France III. Results: Ninety-seven of 253 patients (38%) with ECD had CNS involvement. CNS involvement was significantly associated with a younger age at diagnosis (mean 55.5 years) and at symptom onset (mean 50.5 years), as well as with the presence of the BRAF V600E mutation (in 77% of cases), xanthelasma (34%), and diabetes insipidus (36%). Median survival among patients with CNS involvement was significantly lower than that of patients with ECD without CNS involvement (124 months vs 146 months, p = 0.03). Seventy-four CNS MRIs were centrally reviewed, which showed 3 patterns: tumoral in 66%, pseudo-degenerative in 50%, and vascular in 18%. Targeted therapy (BRAF or MEK inhibitors) was associated with improved symptoms in 43% of patients and MRI improvement in 45%. Conclusions: CNS manifestations are typically associated with poor prognosis in patients with ECD. Three distinct patterns can be recognized: tumoral, pseudodegenerative, and vascular. Classification of evidence: This study provides Class III evidence that targeted therapy leads to clinical or imaging improvement in almost 50% of patients.